2012
DOI: 10.1007/s12178-012-9144-9
|View full text |Cite
|
Sign up to set email alerts
|

Acromioclavicular joint separations

Abstract: Acromioclavicular (AC) joint separations are common injuries of the shoulder girdle, especially in the young and active population. Typically the mechanism of this injury is a direct force against the lateral aspect of the adducted shoulder, the magnitude of which affects injury severity. While low-grade injuries are frequently managed successfully using non-surgical measures, high-grade injuries frequently warrant surgical intervention to minimize pain and maximize shoulder function. Factors such as duration … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
76
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
4

Relationship

3
5

Authors

Journals

citations
Cited by 80 publications
(77 citation statements)
references
References 54 publications
0
76
0
1
Order By: Relevance
“…8,10,11 For most techniques, nonbiologic suture button systems are used for allowing a proper healing process of the graft components. 10,14,20 In a recent study, Scheibel et al 21 described persistent horizontal instability in 41% cases after isolated CC double ligament stabilization.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…8,10,11 For most techniques, nonbiologic suture button systems are used for allowing a proper healing process of the graft components. 10,14,20 In a recent study, Scheibel et al 21 described persistent horizontal instability in 41% cases after isolated CC double ligament stabilization.…”
Section: Discussionmentioning
confidence: 99%
“…9 Today, surgeons widely agree that a biological augmentation is required in chronic cases to enhance the healing potential of the torn structures. 8,10,11 Laboratory studies showed that anatomic reconstruction with double graft tendons showed native-like biomechanical properties 12 and clinical data showed promising results. 9,13 With the progress of arthroscopic techniques, arthroscopically assisted techniques for graft reconstruction of the AC joint have been described.…”
mentioning
confidence: 99%
“…1,2 Although the treatment of Rockwood grade III AC joint injuries is controversial, a recently described subclassification may have helped solve the treatment algorithm with evidence supporting nonoperative treatment of Rockwood grades I, II, and IIIA (horizontally stable) whereas Rockwood grades IIIB (horizontally unstable), IV, V, and VI should be treated with surgical reconstruction. 3 Historically, open procedures have been the dominant surgical treatment strategy, although more recently, arthroscopically assisted techniques have become more popular because of the minimally invasive operation, the enhanced visualization, and the ability to diagnose and treat concomitant glenohumeral pathologies, which are common in higher-grade injuries.…”
mentioning
confidence: 99%
“…9 Additional soft-tissue grafts to reconstruct the CC ligaments are advocated by most investigators for chronic cases, 3,10 whereas others advocate soft-tissue graft reconstruction of the CC ligaments in all cases of surgical AC joint reconstruction, with the goal of achieving improved primary stability. 1,6 Techniques that obviate drill holes in which the softtissue graft is looped around the coracoid and clavicle were developed to decrease the risk of clavicle or coracoid fracture. 9 Despite the advantage of single bone tunnels with a lower fracture risk, these newer techniques had the disadvantage of having a thicker knot stack on top of the clavicle.…”
mentioning
confidence: 99%
“…The ideal management of grade III injuries remains controversial, with many surgeons performing surgery acutely in highlevel athletes and manual laborers. [3][4][5] The original Weaver-Dunn method of AC joint reconstruction has been modified over the past 4 decades, most recently with anatomic coracoclavicular ligament reconstruction with soft-tissue grafts, which have shown superiority on biomechanical testing. 6 Bone tunnels through the clavicle are commonly used to reconstruct the coracoclavicular ligaments; however, they have been associated with a significant decrease in clavicle strength with a subsequent increase in the risk for postoperative fracture.…”
mentioning
confidence: 99%